Upregulation of eIF4E, but not other translation initiation factors, in dendritic spines during memory formation. Issue 11 (27th April 2021) - Gindina, Sofya; Botsford, Benjamin; Cowansage, Kiriana; LeDoux, Joseph; Klann, Eric; Hoeffer, Charles; Ostroff, Linnaea
Abstract: Local translation can provide a rapid, spatially targeted supply of new proteins in distal dendrites to support synaptic changes that underlie learning. Learning and memory are especially sensitive to manipulations of translational control mechanisms, particularly those that target the initiation step, and translation initiation at synapses could be a means of maintaining synapse specificity during plasticity. Initiation predominantly occurs via recruitment of ribosomes to the 5′ mRNA cap by complexes of eukaryotic initiation factors (eIFs), and the interaction between eIF4E and eIF4G1 is a particularly important target of translational control pathways. Pharmacological inhibition of eIF4E–eIF4G1 binding impairs formation of memory for aversive Pavlovian conditioning as well as the accompanying increase in polyribosomes in the heads of dendritic spines in the lateral amygdala (LA). This is consistent with a role for initiation at synapses in memory formation, but whether eIFs are even present near synapses is unknown. To determine whether dendritic spines contain eIFs and whether eIF distribution is affected by learning, we combined immunolabeling with serial section transmission electron microscopy (ssTEM) volume reconstructions of LA dendrites after Pavlovian conditioning. Labeling for eIF4E, eIF4G1, and eIF2α—another key target of regulation—occurred in roughly half of dendritic spines, but learning effects were only found for eIF4E, which was upregulated in the heads of dendritic spines. Our results support the possibility of regulated translation initiation as a means of synapse‐specific protein targeting during learning and are consistent with the model of eIF4E availability as a central point of control. Abstract : Memory formation requires initiation of new protein synthesis as well as protein synthesis in dendrites, but it is unknown whether initiation can happen within dendritic spines. We combined immunolabeling with serial section 3D electron microscopy to examine the distribution of three initiation factors, eIF4E, eIF4G1, and eIF2α in dendritic spines of the lateral amygdala during formation of a Pavlovian conditioning memory. Top row: Electron micrographs showing labeled spines (arrows) with synapses (arrowheads). Bottom left: Segment of dendrite reconstructed from serial sections with synapses shown in red. Bottom right: The percentage of spines containing labeling for eIF4E was higher after training, but there were no differences for eIF4G1 or eIF2α labeling.